Evaluasi Reward Terhadap Kinerja di PT. Sumber Alfaria Trijaya Menggunakan Model Behavior Observation Scale - Wulan Fitriya; Bunga Nabila; Syamsul Hidayat (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to evaluate the effect of the reward system on employee performance at PT. Sumber Alfaria Trijaya using the Behavior Observation Scale (BOS) model. This evaluation is crucial to ensure that the rewards given by the company are able to motivate work enthusiasm and achieve targets optimally. The results of the study indicate that positive work behavior can be reinforced through appropriate and fair rewards, which in turn encourages employees to maintain discipline, responsibility, and achieve targets in accordance with company standards.